Evaluation of spinosad for the oral treatment and control of flea infestations on cats in Europe. Issue 1 (8th December 2014) - Franc, M.; Bouhsira, E.; Böhm, C.; Wolken, S.; Wolf, O.; Löhlein, W.; Wiseman, S.; Hayes, B.; Schnitzler, B.; Fisher, M.
Abstract : Methods: An ectoparasiticide containing spinosad was evaluated as an oral formulation for cats. Two European laboratory studies and a European multicentre field efficacy and safety study assessed the use of a chewable tablet formulation of spinosad at a dose range of 50–75 mg/kg for treatment and control of flea infestations on cats. Results: The studies with experimentally infested cats consistently demonstrated persistent activity against Ctenocephalides felis with >98 per cent efficacy at four weeks post‐treatment. In the field study with naturally infested client‐owned cats from 18 clinics across Germany and Italy, two monthly doses of spinosad were administered; selamectin was the comparator product. Safety was evaluated in 226 cats, each receiving at least one dose of spinosad or selamectin; both products were well tolerated. 113 spinosad‐treated cats and 71 selamectin‐treated cats showed >97 per cent reductions in geometric mean flea counts within 14 days post‐treatment and at 60 days post‐treatment efficacy was >98 per cent in both groups. Analysis of success rates showed 96 per cent in spinosad‐treated cats compared with 90.9 per cent in selamectin‐treated cats at day 60. The spinosad tablets were successfully administered to over 98 percent of cats. These studies indicate that this formulation of spinosad is safe and efficacious for treatment and prevention of flea infestations in cats.